(untitled) (Comprehensive Journal of Science, 2025)
This study presents the design of a natural gas dehydration process using Triethylene Glycol (TEG) for application at the Mellitah Complex. The primary objective is to reduce the water vapor content in natural gas streams to levels that satisfy export specifications and downstream processing requirements, while preventing hydrate formation and corrosion within pipeline networks. An extensive review of previous studies was carried out, following their technical recommendations and extracting critical insights to assess the efficiency and reliability of TEG-based dehydration systems. A dehydration unit with a design capacity of 60 MMscf/d was developed, serving as a simulation model for a large-scale system that could be implemented at the Mellitah industrial facilities. Given the high production rates in Mellitah, TEG dehydration represents an efficient and practical solution for achieving high-purity gas, enhancing operational reliability in offshore gas environments, simplifying maintenance procedures, and reducing operating costs. The process also enables the daily treatment of substantially larger quantities of produced natural gas.